Predicting potential distribution of Quercus suber in Italy based on ecological niche models: Conservation insights and reforestation involvements - Vessella, Federico; Schirone, Bartolomeo (Forest Ecology and Management, 2013)
Different statistical techniques have been used to model species potential distribution related to environ- mental variables. This paper provides a comprehensive assessments of GARP and MaxEnt methods, and investigates for the first time the probability of occurrence of cork oak (Quercus suber L.) in Italy based on ecological niche modelling approaches. A detailed distribution of the species was achieved during a 3- year National Project (SuberItalia) and 17 environmental layers were employed to obtain the potential distribution of cork oak. The performance of the models were measured using the receiver operating characteristic (ROC) approach and Cohen’s Kappa statistic. Results achieved by GARP and MaxEnt showed as the drought and the cold stresses are the main factors affecting cork oak occurrence in Italy. Moreover, the accuracy of the obtained prediction maps were compared to a specifically calibrated geo-statistical method at regional scale, pointing out a preliminary geographical assessment of the suitable surfaces to set apart for cork oak forest expansion in Italy, thereby useful to address reforestation and conserva- tion concerns to face the ongoing area reduction of these forests.
Keywords: Conservation and reforestation areas; Distribution patterns; GARP; Maxent; Quercus suber

Identification of an endophytic Nodulisporium sp from Quercus ilex in central Spain as the anamorph of Biscogniauxia mediterranea by rDNA sequence analysis and effect of different ecological factors on distribution of the fungus - Collado, J.; Platas, G.; Pelaez, F. (MYCOLOGIA, 2001)
A study of fungal endophytes from aerial parts of Quercus ilex ssp. ballota was carried out on 32 specimens sampled at three forests in Central Spain. Trunk bark, fresh leaves, and healthy and decaying twigs were surveyed. A Nodulisporium sp. was frequently recorded among the isolates. Sequence analysis of the internal transcribed spacer (ITS) region of the rDNA (including the 5.8S rRNA gene) was used for the identification of this fungus. The comparison and phylogenetic analysis of the sequences from several representatives of this endophytic species and a group of xylariaceous fungi with Nodulisporium-like anamorphs revealed that the endophytic Nodulisporium sp. was conspecific with the phytopathogenic species Biscogniauxia mediterranea (equivalent to Hypoxylon mediterraneum). Significant differences were found between the isolation frequencies of the fungus, relative to the geographical origin of the samples. Also, the fungus was more frequent on samples collected in the autumn, as compared to those collected in the spring. The greatest degree of colonization was observed in twigs, while in leaves the fungus was present in significantly lower amounts. The relative frequency of this species in bark increased in the higher parts of the trunk. Tissue preference analysis revealed that this fungal species is exclusively located in bark, being absent from xylem of living twigs. The relative abundance of the fungus in decaying twigs was remarkably higher than in healthy twigs.
The following values have no corresponding Zotero field: pub-location: PUBLICATIONS DEPT, BRONX, NY 10458 USA publisher: NEW YORK BOTANICAL GARDEN
Keywords: Distribution patterns; fungal endophytes; Hypoxylon mediterraneum; ITS sequences; Periconiella-like; Xylariaceae

Identification of an endophytic Nodulisporium sp from Quercus ilex in central Spain as the anamorph of Biscogniauxia mediterranea by rDNA sequence analysis and effect of different ecological factors on distribution of the fungus - Collado, J; Platas, G; Pelaez, F (MYCOLOGIA, 2001)
A study of fungal endophytes from aerial parts of Quercus ilex ssp. ballota was carried out on 32 specimens sampled at three forests in Central Spain. Trunk bark, fresh leaves, and healthy and decaying twigs were surveyed. A Nodulisporium sp. was frequently recorded among the isolates. Sequence analysis of the internal transcribed spacer (ITS) region of the rDNA (including the 5.8S rRNA gene) was used for the identification of this fungus. The comparison and phylogenetic analysis of the sequences from several representatives of this endophytic species and a group of xylariaceous fungi with Nodulisporium-like anamorphs revealed that the endophytic Nodulisporium sp. was conspecific with the phytopathogenic species Biscogniauxia mediterranea (equivalent to Hypoxylon mediterraneum). Significant differences were found between the isolation frequencies of the fungus, relative to the geographical origin of the samples. Also, the fungus was more frequent on samples collected in the autumn, as compared to those collected in the spring. The greatest degree of colonization was observed in twigs, while in leaves the fungus was present in significantly lower amounts. The relative frequency of this species in bark increased in the higher parts of the trunk. Tissue preference analysis revealed that this fungal species is exclusively located in bark, being absent from xylem of living twigs. The relative abundance of the fungus in decaying twigs was remarkably higher than in healthy twigs.
Keywords: Distribution patterns; fungal endophytes; Hypoxylon mediterraneum; ITS sequences; Periconiella-like; Xylariaceae

Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer

Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer